Characterization of the InsP(6)-dependent interaction between CK2 and Nopp140 - Lee, Won-Kyu; Lee, Sang-Yeop; Kim, Woo-Il; Rho, Yoon-Hwa; Bae, Young-Seuk; Lee, Cheolju; Kim, Ick Young; Yu, Yeon Gyu (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2008)
Nopp140, a highly phosphorylated nucleolar protein, negatively regulates CK2 a kinase essential for cell, proliferation. We quantitatively analyzed the interaction between two Subunits of CK2 and Nopp140 and characterized the mechanism by which InsP(6) inhibits the interaction. Nopp140 specifically binds to the catalytic subunit of CK2 (CK2 alpha) with a dissociation constant of (K-d) of 4 nM, which interferes with the catalytic activity of CK2. The C-terminal region of Nopp140 is determined as CK2 alpha-binding region by a yeast two-hybrid method as well as a direct measurement of the interaction between CK2 alpha and deletion mutants of Nopp140. InsP6 specifically binds to CK2 alpha and disrupts the interaction between CK2a and Nopp140 with an IC50 value of 25 mu M, thereby attenuating the Nopp140-mediated repression of CK2 activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: PROTEIN-KINASE CK2; CASEIN KINASE-2; BETA-SUBUNIT; INOSITOL HEXAKISPHOSPHATE; NUCLEOLAR PHOSPHOPROTEIN; MASS CHANGES; PHOSPHORYLATION; PYROPHOSPHATES; TRANSCRIPTION; LOCALIZATION